Reading habits across different learning styles of undergraduate students of Faculty of Information Management, Universiti Teknologi Mara, Puncak Perdana Campus, Shah Alam / Siti Rohayu Mamat@Abdul Rashid - Mamat@Abdul Rashid, Siti Rohayu (2010)
This study aims to identify the reading habits across different learning styles amongst undergraduate students of FPM. The study used a survey approach in collecting data.Questionnaire were administered to 332 sample population, 330 responses were found usable. The study comprises students from four programmes in FPM namely IS220, IS221, IS222 and IS223. The findings show that web sites have become increasingly important reading materials as well as the Internet as mostly accessed sources of reading. Disappointingly, majority of students spend only one to three hours of their time for reading weekly and they usually read at night. The students normally read for the purpose of achieving better result and to complete tasks. In terms of learning styles, the findings indicate that the highest number of students is kinesthetic learner. There is no significant difference found between students' reading habits and reading attitudes and the three types of learning styles of the students in this study. Several limitations of the study were identified related to the small sample size and the limited number of variables studied. In general, the findings of the study should contribute towards the improvement of curriculum design by the faculty and services provided by the library in order to support the students to become active readers